Political Communication of Indonesian Presidential Candidates on Social Media - Dawam, Dawam; Ihsan, Zainal; Darmawan, Ferry (Indonesian Scientific Journal (Jurnal Ilmiah Indonesia), 2024)
Social media has become a very important tool in political communication, especially in the face of presidential election contestation. This study aims to analyze Anies Baswedan's political communication on social media ahead of the 2024 presidential election. Using a qualitative approach and content analysis method, this study examines Anies Baswedan's political communication content on social media platforms such as Twitter, Instagram, Facebook, and YouTube. The results showed that Anies Baswedan raised various themes and main issues in his political communication on social media, such as the economy, education, health, infrastructure, corruption, and environment. He uses a critical and vocal communication style in voicing opinions and criticizing government policies. His communication strategy also includes efforts to image himself as a leader who is vocal, critical, close to the people, experienced, competent, and concerned about environmental issues and sustainable development. Anies Baswedan's political communication on social media received diverse responses from audiences, ranging from support to intense criticism and debate. However, political communication on social media also faces a number of challenges and implications, such as political polarization, the spread of false information, black campaigns, and issues of digital campaign ethics.